Performance Analysis of Public Transport in Gianyar Regency - Ida Bagus Wirahaji; I Ketut Sutapa; I Gede Fery Surya Tapa (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
The performance of an urban public transport plays an important role in accommodating population mobility and realizing sustainable transportation. The performance of public transport can be influenced by several factors, including the quality of public transport services themselves and the accessibility of the roads they pass. Service quality concerns arrival frequency, waiting time, travel time and so on. Road accessibility is influenced by the presence of side barriers, such as parking vehicles on the road, vehicles in and out, slow vehicles, and so on. This study analyzes the exogenous latent variables of Service Quality and Road Accessibility that affect the endogenous variables of Public Transportation Performance in Gianyar Regency, especially on the Batubulan-Ubud Terminal Route. The method of collecting community perception data is by distributing 250 questionnaires to respondents who live along the Batubulan-Ubud Terminal Route Corridor. The data analysis method used Statistical Equation Modeling (SEM) AMOS. Validity and reliability tests were carried out using the confirmatory factor analysis (CFA) method. Based on the results of the analysis, it was found that the quality of public transportation services had a significant positive effect, with p value = 0.18 <0.05, path coefficient 0.049. Road accessibility also has a significant positive effect, with p value = 0.035 < 0.05, coefficient. line 0.225. The Goodness of Fit test also fulfills parameters such as: Chi-square count 66.27 < Chi-square table 81.381; Probability 0.332 0.05; CMIN/DF 1.069 2.00; GFI 0.961 0.960; AGFI 0.943 0.90; TLI 0.995 0.950; CFI 0.995 0.95; RMSEA 0.000 0.08 all meet. The performance of public transportation on the Batubulan-Ubud Terminal Route is considered very bad due to poor service quality and road accessibility.